Prospects and determinants of adoption of IITA plantain and banana based technologies in three Niger Delta States of Nigeria - Faturoti, B.O.; Emah, G.N.; Isife, B.I.; Tenkouano, A.; Lemchi, J. (2006)
High yielding and disease resistant plantain and banana hybrids and its associated technologies generated by IITA to combat the menace of black Sigatoka disease (Mycosphaerella fijiensis) were massively disseminated in year 2000. Since the hybrids were slightly different from the existing varieties in fruit size there was a need to assess thier prospects. Structured questionnaire and interview schedule were used to collect data on the adoption of the fourteen disseminated innovations among 85 randomly selected farmers in 15 villages drawn from the three states. Correlation analysis was used to test the strength of relationship between the respondents personal and socio economic factors, the variables investigated and the adoption index. The results showed that all the respondents adopted at least one of the 14 disseminated innovations. Average adoption level was 40.33% ranging from Rivers 36%, Akwa-Ibom 38% and Bayelsa 47%. The adoption process was strongly influenced by household size, educational attainment, farming experience, frequency of extension visit, overall experience from innovation, market access, access to credit and profit as a result of the technology. It was concluded that the high level of adoption of the technology was not unconnected with the induced model of adoption where farmers saw the yield before embarking on the cultivation and the support (educational and material incentive) received from the disseminating institutions.